Risk factors of retinal vein occlusion in East Asia: a meta-analysis - Qiu, Xinyue; Jiao, Ziman; Liu, Yuxin; Zhou, Yunhao; Li, Haiyu; Chen, Xin; Liu, Guanghui (Frontiers in Ophthalmology, 2025)
ObjectiveWith the intention of developing a more targeted control strategy for retinal vein occlusion (RVO) in East Asian populations, a meta-analysis was conducted to evaluate the risk factors associated with RVO in this region.MethodsPubMed, Web of Science, Cochrane Library, CNKI, Wanfang and VIP databases were searched for studies that reported risk factors of RVO in East Asia, published from the establishment of the database to May 2024. To further filter the articles, Newcastle-Ottawa Scale (NOS) evaluation method was utilized to assess the quality of selected articles. After valid data were extracted, Meta-analysis was performed by Review Manager software.ResultsA total of 21 literatures were included, including 27561 cases in the RVO group (Case group) and 514578 cases in the non-retinal vein occlusion (NRVO) group (Control group). Results of meta-analysis showed that chronic kidney disease [odds ratio (OR)=4.14, 95% confidence interval (CI): (1.86%, 9.24%)], hypertension [OR=4.11, 95% CI: (3.09%, 5.48%)], hyperlipidemia [OR=3.45, 95%CI: (2.32%, 5.12%)], diabetes mellitus [OR=3.00, 95%CI: (1.88%, 4.80%)], homocysteine [OR=0.87, 95%CI: (0.59%, 1.15%)], have statistically significant differences between the RVO group and the NRVO group(P<0.05).ConclusionThe occurrence of RVO is closely related to its risk factors, such as chronic kidney disease, hypertension, hyperlipidemia, diabetes mellitus and high homocysteine. In the process of diagnosis and treatment of RVO, doctors should focus on the above risk factors to prevent the occurrence of the disease.